Selection Criteria for an Enterprise Resource Planning (ERP) System for a Business Organization - Gunathilaka, T.A. (NSBM Green University, 2022)
Enterprise Resource Planning (ERP) system performance highly affects the organization's performance. Whether it is the right product or not should be decided before purchasing the software. Selection of the right and most suitable ERP system is a challenge in today’s business environment. Some ERP having more functionalities not required for your business organization, some having limited functionalities not satisfied with the minimum requirements. The organization needs to be adjusted or customized and match with the available product. Selection a right product to your organization saves lot of money, time, resources ultimately making better performance. In this article describe how do we select right ERP’s, what are the factors should be considered when selecting a good ERP system.